First, we can use these rules for exponents to simplify the two terms in parenthesis:
#a = a^color(red)(1)# and #(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#
#(-2x^2)^2 * (x^2)^-1 =>#
#(-2^color(red)(1)x^color(red)(2))^color(blue)(2) * (x^color(red)(2))^color(blue)(-1) =>#
#(-2^(color(red)(1)xxcolor(blue)(2))x^(color(red)(2)xxcolor(blue)(2))) * x^(color(red)(2)xxcolor(blue)(-1)) =>#
#(-2^2x^4) * x^-2 =>#
#(4x^4) * x^-2#
Next, we can rewrite this expression as:
#4(x^4 * x^-2)#
Now, we can use this rule for exponents to complete the simplification as:
#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#
#4(x^color(red)(4) * x^color(blue)(-2)) =>#
#4x^(color(red)(4) + color(blue)(-2)) =>#
#4x^(color(red)(4) - color(blue)(2)) =>#
#4x^2#